Jaroslav Olša, jr.: 150 Years of Hidden Ties Between Koreans and Czechs (Czech Journal of International Relations, 2021)
1ST EDITION. PRAGUE: NOVÁ VLNA, 2020, 164 PAGES,ISBN 978-80-88343-14-1Chapters from the history of contacts between the Czech Lands and the Korean Peninsula.